2009
DOI: 10.1158/1055-9965.epi-08-1193
|View full text |Cite
|
Sign up to set email alerts
|

One-Carbon Metabolism and Prostate Cancer Risk: Prospective Investigation of Seven Circulating B Vitamins and Metabolites

Abstract: Purpose: Components of one-carbon metabolism are believed to influence cancer development with suggested mechanisms, including DNA methylation and DNA repair mechanisms. However, few prospective studies have investigated one-carbon metabolism in relation to prostate cancer risk, and the results have been conflicting. The aim of this study was to do a comprehensive investigation of the components of onecarbon metabolism in relation to prostate cancer risk. A panel of seven circulating B vitamins and related met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 34 publications
7
56
3
1
Order By: Relevance
“…10,11 Nevertheless, an observational population-based study previously showed positive associations of prostate cancer risk with circulating choline and vitamin B2, and a nonsignificant positive association with plasma betaine concentration. 12 These observations may support the hypothesis that high methyl group bioavailability plays a role in cancer development.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…10,11 Nevertheless, an observational population-based study previously showed positive associations of prostate cancer risk with circulating choline and vitamin B2, and a nonsignificant positive association with plasma betaine concentration. 12 These observations may support the hypothesis that high methyl group bioavailability plays a role in cancer development.…”
supporting
confidence: 61%
“…12 In our study population, high serum folate concentration was associated with modestly increased prostate cancer risk. 40 In addition, here we observed that high serine was associated with increased prostate cancer risk when folate status is low, and that for sarcosine and glycine, the inverse associations were only observed in combination with high folate status.…”
Section: One-carbon Balance and Prostate Cancermentioning
confidence: 58%
“…Secondary analyses of the Aspirin/ Folate Polyp Prevention Study demonstrated that individuals treated with folic acid had an increased risk of prostate cancer (Figueiredo et al 2009). Notably, in the Northern Sweden Health and Disease Cohort, doubling of plasma choline was associated with 46% increase of prostate cancer risk (Johansson et al 2009). These findings point to a possible role of one-carbon metabolism in growth enhancement of prostate cancer.…”
Section: Cancermentioning
confidence: 99%
“…FA supplementation was associated with a 2.6 fold increase in incidence (Figueiredo et al, 2009) and stage (Lawson et al, 2007) of prostate tumors. Collin noted serum folate-related increase in PSA velocity Others related high B12 levels to prostate cancer (Hultdin et al, 2005;Johansson et al, 2009;Weinstein et al, 2006;Vlajinac et al, 1997). We reported direct stimulation of prostate cancer by administration of B12 to a B12 deficient patient (Tisman et al, 2009) and by a supplement containing a combination of B12 and mixed folates Figures 3 and 4 (Tisman & Garcia, 2011).…”
Section: Contemporary Observations Spur Interest In Folate B12 and Pmentioning
confidence: 80%